Fungal communities in different aged leaves of Eucalyptus microcorys F. Muell - Lacerda, Lorena Tigre [UNESP]; Gusmão, Luís Fernando Pascholati; Rodrigues, Andre [UNESP] (Springer Nature, 2019)
Brazil is the world’s largest producer of “eucalyptus” and its highest number of species in the country is located at the “Floresta Estadual Edmundo Navarro de Andrade” (FEENA). Despite the historic and economic importance of this area, little is known about the fungal community associated with Eucalyptus species at FEENA. Here we evaluated the diversity of saprobic fungi in three different stages of Eucalyptus microcorys F. Muell leaf litter. In addition, we compared the saprotrophic fungal community with endophytic fungi of E. microcorys to assess whether endophytes are also found in the leaf litter. We investigated fungal communities using the particle filtration technique coupled with isolation on two culture media. Fungal isolates were clustered into morphospecies and identified using both morphology and DNA sequences. A total of 2558 fungal isolates were obtained, represented by 48 taxa. We report the following five species for the first time for the American continent: Castanediella eucalypti Crous, Hern.-Restr. & M.J. Wingf., Harknessia pseudohawaiiensis Crous & Carnegie, Neophaemoniella eucalypti Roon.-Lath. & Crous, N. niveniae (Crous) Crous, Xenogliocladiopsis cypellocarpae L. Lombard & Crous and Xyladictyochaeta lusitanica Hern.-Restr., R.F. Castañeda & Gené. In addition, we found putative new species and well-known fungal pathogens of “eucalyptus” in the leaf litter. The fungal diversity decreased, while the dominance of certain fungal species increased across leaf stages. As expected, the endophytic fungal community significantly differed from communities in the leaf litter. Particularly, only 8 taxa were shared between the leaf types. Eucalyptus microcorys hosts a fairly diverse saprobic fungal community on its leaves, which varies with leaf maturity. Exploring the saprobic fungal community is essential for understanding its dynamics in the leaf litter and the trophic interactions with their plant hosts.
Keywords: Diversity; Fungi; Leaf litter; Particle filtration; Saprotrophs